The Influence of Brand Image and Social Media on Purchase Decision Cognition with Interest to Buy as Intervening Variable - Yusriana, Chinthia Sari (LPPM Universitas Bina Bangsa, 2024)
During the COVID -19 pandemic, people were enthusiastic about consuming vitamins, with the aim of increasing body resistance, especially to protect the body from COVID-19. Therefore, this study seeks to determine the factors that influence cognitive purchasing decisions, especially for Imboost products, such as the role of social media, brand image, and buying interest.Research respondents are boost consumers in the Yogyakarta area. The number of samples is 90 with online questionnaire distribution techniques, but the data that can be processed is 81. Data analysis using Smart PLS. The results of the analysis show that Brand Image has a significant positive effect on Purchase Interest and Purchase Decision Cognition. Social Media has an effect on Buying Interest. Meanwhile, Social Media has no effect on Cognitive Purchase Decisions, but is mediated by buying interest. Furthermore, the buying interest hypothesis is proven to have a positive influence on Cognitive Purchase Decisions.The results of this study provide managerial implications, especially for the marketing strategy of boost products. Cognitive purchasing decisions on imboost products require complete learning of imboost products because these products involve physical health